Development of a method of increasing the interference immunity of frequency-hopping spread spectrum radio communication devices - Kuvshynov, Oleksii; Shyshatskyi, Andrii; Zhuk, Olesia; Bieliakov, Robert; Prokopenko, Yevgen; Leontiev, Oleksii; Zhyvotovskyi, Ruslan; Drobakha, Hryhorii; Romanenko, Igor; Petruk, Sergii (Eastern-European Journal of Enterprise Technologies, 2019)
The development of a technique for increasing the interference immunity of frequency-hopping spread spectrum radio communication equipment has been carried out. The essence of the proposed method is the rational distribution of operating frequencies among the frequency-hopping spread spectrum radio communication devices, taking into account the mutual influence of transceivers on each other. The technique takes into account the strategies of the electronic warfare complex, predicts the signal-interference environment, chooses the parameters of the frequency-hopping spread spectrum, depending on the parameters of the frequency range. The existing scientific-methodical apparatus is intended only for use in radio directions and does not take into account a number of important parameters that does not allow it to be used with a lack of radio resources and active electronic countermeasure. According to the results of the research, it has been found that the proposed method allows increasing the interference immunity of frequency-hopping spread spectrum radio communication equipment on average up to 30 %, depending on the state of the channel. However, an increase in computing complexity at the level of 10 % is noted due to the introduction of additional procedures. Additional procedures in the developed method are the distribution of frequencies in the network, calculation of the mutual influence of transceivers of frequency-hopping radio communication devices on each other, prediction of the signal-interference situation and selection of frequency-hopping parameters. It is advisable to use this methodology in radio stations with programmable architecture to increase their interference immunity due to the rational distribution of operating frequencies of frequency-hopping spread spectrum radio communication devices in the network and forecasting of the signal situation